2017
DOI: 10.1038/s41598-017-14480-z
|View full text |Cite
|
Sign up to set email alerts
|

Surface reactivity of amphibole asbestos: a comparison between crocidolite and tremolite

Abstract: Among asbestos minerals, fibrous riebeckite (crocidolite) and tremolite share the amphibole structure but largely differ in terms of their iron content and oxidation state. In asbestos toxicology, iron-generated free radicals are largely held as one of the causes of asbestos malignant effect. With the aim of clarifying i) the relationship between Fe occurrence and asbestos surface reactivity, and ii) how free-radical generation is modulated by surface modifications of the minerals, UICC crocidolite and fibrous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 32 publications
7
24
0
Order By: Relevance
“…Within this study we also sought if incubation in simulated biological fluids could cause modifications in free radical generation. Such an evolution over time has been reported previously in relation to amphiboles (Andreozzi et al 2017). Analysis of intrinsic ROS production by EPR showed no significant increase over vehicle control for any of the test samples indicating, that for the spin-trap Tempone-H at least, reactivity is minimal.…”
Section: Surface Reactivitysupporting
confidence: 84%
“…Within this study we also sought if incubation in simulated biological fluids could cause modifications in free radical generation. Such an evolution over time has been reported previously in relation to amphiboles (Andreozzi et al 2017). Analysis of intrinsic ROS production by EPR showed no significant increase over vehicle control for any of the test samples indicating, that for the spin-trap Tempone-H at least, reactivity is minimal.…”
Section: Surface Reactivitysupporting
confidence: 84%
“…By geological classification, asbestos fibres are defined as having aspect ratio ≥3:1, length ≥5 μm, and width <0.25 μm. 6 This does not account for cleavage fragments, or high potency shorter fibres. 9 This asbestos classification was created to facilitate the counting of the MF using standard microscopy methods and was not based on the potency of these segments or shorter fibres to induce ARD.…”
Section: Introductionmentioning
confidence: 99%
“…By geological classification, asbestos fibres are defined as having aspect ratio ≥3:1, length ≥5 μm, and width <0.25 μm 6 . This does not account for cleavage fragments, or high potency shorter fibres 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, a recent study performed by our group on the pathogenic-related fibre surface reactivity of riebeckite and tremolite showed that both fibrous amphiboles have sustained radical production, even when highly altered by oxidative leaching. In particular, tremolite exhibited a significant radical production from both pristine and altered fibres (Andreozzi et al, 2017). Differently from riebeckite, the generally small iron content of tremolite makes potentially difficult a detailed analysis of subtle modifications of the iron site allocation and variation of its oxidation state.…”
Section: Introductionmentioning
confidence: 99%